Impurities contained in antifungal drug ketoconazole are potent activators of human aryl hydrocarbon receptor - Grycová, Aneta; Dořičáková, Aneta; Dvořák, Zdeněk (Toxicology letters, 2015)
Antifungal drug ketoconazole is a mixture of (+)/(-) cis-enantiomers, which also contains several impurities. Ketoconazole was identified as an activator of aryl hydrocarbon receptor AhR by three independent research teams. In the current paper we demonstrate that impurities contained in ketoconazole preparations are strong activators of human AhR and inducers of CYP1A1. Impurity IMP-C had similar potency (EC50), but 10-15 times higher efficacy (magnitude of induction) towards AhR, comparing to (+)-ketoconazole, as revealed by gene reporter assay in AZ-AHR stably transfected cells. Impurities IMP-B and IMP-C, and in lesser extent IMP-E, induced a formation of AhR-DNA complex, as demonstrated by electromobility shift assay EMSA. Impurities IMP-C and IMP-E dose-dependently induced CYP1A1 mRNA after 24 h, and their effects were comparable to those by (+)-ketoconazole. The level of CYP1A1 protein in HepG2 cells was strongly increased by IMP-C after 48h. In conclusion, our data further elucidated molecular effects of ketoconazole towards AhR signaling pathway, with possible implications in ketoconazole role in skin chemoprevention and/or damage, involving AhR.
Keywords: molekulární struktura; Enzyme Induction; Antifungal drugs; Humans; Drug Contamination; Antifungal Agents; lidé; buňky Hep G2; Dioxin receptor; receptory aromatických uhlovodíků; ketokonazol; antifungální látky; Cytochrome P450; Drug–drug interactions; Hep G2 Cells; Cytochrome P-450 CYP1A1; Molecular Structure; enzymová indukce; Receptors, Aryl Hydrocarbon; cytochrom P-450 CYP1A1; Ketoconazole; kontaminace léku